Pengaruh Kecerdasan Emosional, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Probolinggo - Moidi, Erika Triwahyu; Bahri, Mohammad Saiful; Yatiningrum, Agung (Universitas Panca Marga, 2024)
The study aims to determine the extent to which the variables of emotional intelligence, work discipline and work motivation affect employee performance at BKPSDM Probolinggo City both simultaneously, partially, and dominantly. The type of research used is a quantitative research method with a causal relationship. The variables studied are emotional intelligence, work discipline, work motivation and employee performance, with a total of 43 respondents. The data analysis method from the research results is a quantitative description method using SPSS in the form of validity tests, reliability, classical assumption tests, multiple linear regression analysis, coefficient of determination, hypothesis testing. The results of the study are shown by the multiple regression equation Y = 3.558 + 0.428X2 + 0.202X2 + 0.220X3 + 2.481. The results of the simultaneous hypothesis test Fcount 38.865> Ftable 2.85 with a Sig. value of 0.000 <0.05. This means that there is an influence of emotional intelligence, work discipline and work motivation simultaneously on employee performance. For the results of the partial hypothesis test, the t-count value, X1 = 6.623, X2 = 2.424, X3 = 2.456 > t table = 2.0225 with the Sig. value of the four variables <0.025. This means that there is an influence of emotional intelligence, work discipline and work motivation partially on employee performance. The results of the dominant hypothesis test show that the emotional intelligence variable (X1) has a greater beta coefficient value than other independent variables